If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 = 6x + -5 Reorder the terms: 49 = -5 + 6x Solving 49 = -5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 49 + -6x = -5 + 6x + -6x Combine like terms: 6x + -6x = 0 49 + -6x = -5 + 0 49 + -6x = -5 Add '-49' to each side of the equation. 49 + -49 + -6x = -5 + -49 Combine like terms: 49 + -49 = 0 0 + -6x = -5 + -49 -6x = -5 + -49 Combine like terms: -5 + -49 = -54 -6x = -54 Divide each side by '-6'. x = 9 Simplifying x = 9
| 7x+3+2=16+3 | | 2x-5=9x-25 | | (1x)(4x)=1500 | | 26x(x+3)=3380 | | (1x)(4x)=1 | | 8+8x=85+x | | 5x-7=38 | | 3x=2x+18 | | 6x+28=13x-28 | | -19-5X=5-9X | | 17+n=14+3 | | x^4+5x^3+20x^2+60x=-116 | | -8+5x=-12x-1 | | 111-5X=10X+21 | | 10x-29=51 | | 5X+12=93+4X | | 8+11X=98+X | | 5x+13y=126 | | 2(3+3x)=6x+6 | | 2x+3x+6=10x-16 | | 3x+5y=70 | | 6x+31=14x-65 | | 4(x-8)=25.6 | | 6(a+1)=58.2 | | 6(a+1)= | | 8A+8B=-16 | | h=-16t^2+56+1 | | h=-16t^2+70t+10 | | -0.5=3c-5 | | 4x-10=4-x | | 7t-4=10t+14 | | 4x+12=7x+3 |